The Effectiveness of WhatsApp Blast Content in Fundraising Efforts at the MDMC (Muhammadiyah Disaster Management Center) Non-Profit Organization - Yuan Shiva Dahlia; Erwin Rasyid; Dinara Maya Julijanti (Universitas Lambung Mangkurat, 2025)
This study examines the effectiveness of WhatsApp Blast content in supporting fundraising efforts at the non-profit organization MDMC (Muhammadiyah Disaster Management Center). Using a descriptive quantitative approach, data were collected from 98 respondents who received MDMC’s WhatsApp Blast messages. The study applies the AIDA model (Attention, Interest, Desire, Action) to assess the persuasive stages of the messages and integrates the Shannon and Weaver communication model to evaluate message delivery and potential communication noise. The results show a positive and statistically significant relationship between WhatsApp Blast effectiveness and fundraising outcomes (r = 0.274; p < 0.01); however, the relationship is substantively weak. The coefficient of determination (r² = 0.075) indicates that WhatsApp Blast contributes only minimally to fundraising success. The findings further reveal that WhatsApp Blast is effective primarily in generating attention and interest, but less effective in stimulating desire and encouraging donation actions due to limited emotional depth, insufficient personalization, and the presence of semantic noise. This study fills a research gap by examining WhatsApp Blast as a closed and direct communication channel for nonprofit fundraising, which remains underexplored compared to open social media platforms. The study highlights the importance of emotional engagement, message clarity, and multi-channel integration in strengthening digital fundraising strategies for nonprofit organizations.